2022
DOI: 10.1136/ijgc-2022-003981
|View full text |Cite
|
Sign up to set email alerts
|

Case-mix adjustment to compare hospital performances regarding complications after cytoreductive surgery for ovarian cancer: a nationwide population-based study

Abstract: ObjectiveComplication rates after cytoreductive surgery are important quality indicators for hospitals that treat patients with advanced-stage ovarian cancer. Case-mix factors are patient and tumor characteristics that may influence hospital outcomes such as the complication rates. Currently, no case-mix adjustment model exists for complications after cytoreductive surgery; therefore, it is unclear whether hospitals are being compared correctly. This study aims to develop the first case-mix adjustment model fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…However, recent publications indicate that the use of CR data for quality assessment at the HCP level is just beginning. In the Netherlands, hospital comparisons based on quality indicators have already been published for gynaecological cancers [29][30][31], lung cancer [32] or rectal cancer [33]. Such analyses, like ours, show that cancer care can be made measurable at the HCP level and that fair benchmarking of specific clinical aspects is possible.…”
Section: Discussionsupporting
confidence: 53%
“…However, recent publications indicate that the use of CR data for quality assessment at the HCP level is just beginning. In the Netherlands, hospital comparisons based on quality indicators have already been published for gynaecological cancers [29][30][31], lung cancer [32] or rectal cancer [33]. Such analyses, like ours, show that cancer care can be made measurable at the HCP level and that fair benchmarking of specific clinical aspects is possible.…”
Section: Discussionsupporting
confidence: 53%
“…The authors of 22 studies (25%) reported feeding the results back to the groups (that is hospitals or regions) they studied (see Table S5 for details) 14 , 21 , 22 , 33 , 37 , 42–44 , 46 , 47 , 49 , 50 , 52 , 53 , 57 , 64 , 71 , 73 , 78 , 81 , 83 , 84 , whereas 67 studies (75%) made no mention of feeding the results back to the hospitals or regions studied. Those authors who did report providing feedback fed the results into quality improvement efforts at the regional (9; 39%) or national (6; 27%) level, sent the results to all studied groups (4; 18%), or both sent the results to all studied groups and fed the results into quality improvement efforts (3; 13%).…”
Section: Resultsmentioning
confidence: 99%